Prognostic Value of Inflammatory and Nutritional Indicators in Non-Metastatic Soft Tissue Sarcomas - Yan Y; Zhang Y; Chen Y; Zhong G; Huang W; Zhang Y (Journal of Inflammation Research)
Yuan Yan,1– 3,* Yunhui Zhang,1– 3,* Yonghan Chen,1– 3,* Guoqing Zhong,2,3 Wenhan Huang,2,3 Yu Zhang1– 3 1School of Medicine, South China University of Technology, Guangzhou, Guangdong, People’s Republic of China; 2Department of Orthopaedics Oncology, Guangdong Provincial People’s Hospital (Guangdong Academy of Medical Sciences), Southern Medical University, Guangzhou, Guangdong, People’s Republic of China; 3School of Materials Science and Engineering (National Engineering Research Center for Tissue Restoration and Reconstruction), South China University of Technology, Guangzhou, Guangdong, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yu Zhang; Wenhan Huang, Guangdong Provincial People’s Hospital, Guangdong Academy of Medical Sciences, Zhongshan 2nd Road, Guangzhou, Guangdong, People’s Republic of China, Email luck_2001@126.com; wenhanx@126.comBackground: Soft tissue sarcoma (STS) has lacked reliable prognostic indicators. This study evaluates blood-based inflammatory and nutritional indexes to identify good predictors for STS outcomes. These indicators included neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), lymphocyte-to-monocyte ratio (LMR), systemic inflammation response index (SIRI), lymphocyte-to-monocyte ratio (PNI), albumin-to-globulin ratio (AGR), and platelet-to-albumin ratio (PAR).Methods: A total of 93 were included, and blood indexes were measured preoperatively. Univariate and multivariate regression analyses identified significant predictors, and model performance was assessed using the Akaike Information Criterion (AIC), Bayesian Information Criterion (BIC), Concordance Index (C-index), and Likelihood Ratio Chi-Square (LR_χ 2).Results: Univariate analysis indicated that NLR, PLR, LMR, SIRI, AGR, and PAR show potentially significant differences (P< 0.01), except for PNI. Further analysis showed that SIRI and AGR have a high C-index, LR_χ 2, and − 2 log-likelihood, lower AIC and BIC, indicating a better model fit for overall survival (OS) and disease-free survival (DFS). The combination index of the SIRI+AGR+Enneking stage achieved the best accuracy (C-index: 0.751 for DFS; C-index: 0.755 for OS). Multivariate regression showed higher Enneking staging (HR=2.720, P=0.038), lower AGR (HR=2.091, P=0.014), and higher SIRI (HR=2.078, P=0.034) as independent prognostic factors for DFS. Meanwhile, low AGR (HR=3.729, P=0.034), and high SIRI (HR=3.729, P=0.016) remained independent prognostic factors for OS.Conclusion: Preoperative SIRI is a better predictive index compared to NLR, PLR, and LMR. Preoperative SIRI and AGR are independent risk factors for both DFS and OS. The combination index of the SIRI+AGR+Enneking stage provides a more robust prediction of clinical prognosis in STS patients.Keywords: soft tissue sarcoma, prognostic index, inflammatory, survival analysis